Conservation biology and conservation paleobiology meet the Anthropocene together: history matters - Walker, Sally E. (Frontiers in Earth Science, 2023)
As a species, we have reached a tipping point for Earth derived from our unsustainable resource use. While conservation efforts occurred early in human civilization, it was not until 1980 that the full force of environmental destruction, including the Santa Barbara oil spill in the 1970s, culminated in the new discipline of conservation biology focused on the biosphere. Similarly, conservation paleobiology, named two decades later, brings the unique perspective of the fossil record to conservation efforts, uniting biosphere and geosphere scientists. To date, conservation history does not include paleontological or geological perspectives. Further, each discipline has a different benchmark— near time— for when Earth’s ecosystems were modified by humans. Accordingly, the history of conservation efforts leading up to conservation biology and conservation paleobiology was examined from a geological and ecological framework. To provide a benchmark for near time, the hominin record and their geo-environmental modifications were also examined and revealed that by the start of the Holocene, all continents except ice-covered Antarctica and Greenland had human-modified ecosystems. Therefore, near time is dispensable when the Holocene Epoch is universally understood and precisely defined as a time when H. sapiens dominated environments. Lastly, a conservation corps is urgently needed, following the long tradition of F.D. R.’s Civilian Conservation Corps of the 1930s and J.F. Kennedy’s Peace Corps of the 1960s, to promote a global network connecting all students and practitioners of conservation disciplines to focus on biotic resilience, recovery, and solutions for the world’s most pressing environmental problems.